PENGUKURAN TERHADAP PENGGUNAAN TEKNOLOGI INFORMASI AUDIT DAN PERSEPSI KEGUNAAN - Yosua Carisma; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
Information technology today is growing very rapidly so that information technology plays an important role and become a staple of the human. This research aims to examine the use of information technology auditing and perceived importance. This research is a replication of the research that has been done by Janvrin et al (2008) in the United States with some modifications due to differences in the location of the object population, and methods of analysis. Totally responden of 46 auditors who work in the public accountant Bigfour and non Bigfour used in this study. Data analysis method that has been used is Partial Least Square with statistical programs SmartPLS 2.0 M3. This research is expected to measure the importance of the use of information technology audit so that it can directly affect the audit assessment and the effectiveness and efficiency of the work of auditors. The result of this researchindicate that perceived usefulness has a positive and significant influence with the examination of the use of information technology and the importance of perception.